EDUKASI ZAKAT, INFAQ DAN SHADAQOH (ZIS) PADA SISWA/SISWI SMA MUHAMMADIYAH 1 BENGKULU - Tohirin Tohirin; Zamahsari Zamahsari (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2019)
Zakat is not the only practice that is a form of obedience to the rules of God as an embodiment of faith in God (dimension hablum minallah). But also as an instrument for poverty alleviation and equitable economic growth (hablun minannas). A Muslim who makes zakat does not only purify his soul and wealth, but also the welfare of the recipient and the community. Some of the wisdom of paying zakat, infaq, and shadaqah (ZIS) is avoiding social inequality, cleaning up and eroding bad morals, developing the potential of the Ummah, a means to clean up wealth, a form of gratitude for the pleasure of Allah SWT, and moral support for converts. In addition to zakat, there are other forms of expenditure that are not tied to the amount (nishab) and time (haul) that are voluntary namely infaq and shadaqah. If appropriately managed ZIS will be an extraordinary tool in the development of the people. For this reason, ZIS education is important to do early on so that it becomes a habit and awareness.